Semi-auto grass cutter with IOT control / Muhammad Irfan Daniel Mohd Salleh - Mohd Salleh, Muhammad Irfan Daniel (2024)
The semi-auto grass cutter with IoT control represents an innovative fusion of cutting-edge technology and lawn care, offering a convenient and efficient solution for maintaining outdoor spaces. Through the integration of Internet of Things (IoT) capabilities, users can remotely control the grass cutter using smartphones or tablets, eliminating the need for manual effort. This visionary project incorporates various components such as sensors, motors, and IoT modules, working in unison to enable remote control and enhance user convenience. The grass cutter's obstacle detection mechanism relies on an ultrasonic sensor, designed to alert users when an obstacle is within a 1-meter range by activating a buzzer. This feature ensures precise and efficient cutting while keeping users informed of potential impediments during operation. The IoT module seamlessly facilitates wireless communication, granting users flexibility in managing lawn care tasks. The benefits of this semi-automatic grass cutter with IoT control are numerous. Users can easily control the grass cutter via mobile devices. The ultrasonic sensor, serving as the obstacle detector, enhances safety and awareness by promptly notifying users of obstacles in the mower's path. The integration of IoT technology continues to offer real-time monitoring and data collection, providing valuable insights into lawn care patterns for informed decision-making. This semi-automatic grass cutter with IoT control, featuring an ultrasonic sensor for obstacle detection, not only simplifies lawn maintenance but also prioritizes user safety and awareness, contributing to an overall enhanced lawn care experience